Respon Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L.) Terhadap Pemberian Pupuk Kandang Ayam dan Pupuk Organik Cair (POC) Daun Kelor - Muhammad Ridho; Dermawan Hutagaol; Nurma Ani (Jurnal Agrofolium, 2023)
Peanut is the most important agricultural commodity after soybean which has a strategic role in the national food as a source of protein and vegetable oil in Indonesia. This study aims to determine the application of chicken manure and liquid organic fertilizer (POC) on the growth and production of peanuts (Arachis hypogaea L.) and the interaction of chicken manure and liquid organic fertilizer (POC) on Moringa leaves. This research was conducted from April to June 2022. This study used a Factorial Randomized Block Design with 2 factors studied and 3 repetitions where the first factor was chicken manure (A) which consisted of 3 levels, namely A0 = no treatment (control), A1 = 1.9 kg plot-1, and A2 = 3.8 kg plot-1. The second factor was liquid organic fertilizer (K) for Moringa leaves which consisted of 3 levels, namely K0 = no treatment (control), K1 = 150 ml liter-1 water plot-1 (10 tonnes ha-1), K2 = 300 ml liter-1 water/slot and K3 = 450 ml liter-1 of water plot-1. The results showed that the application of chicken manure had a very significant effect on the parameters of pod weight per sample plant and pod weight per plot, but had no significant effect on the parameters of plant height and the weight of 100 dry seeds plot-1. The application of liquid organic fertilizer (POC) to Moringa leaves had a significant effect on the parameters of pod weight per sample plant and pod weight plot-1, but had no significant effect on the parameters of plant height and weight of 100 dry seeds plot-1. . . The interaction of the application of chicken manure and liquid organic fertilizer (POC) of Moringa leaves did not significantly affect all observation parameters.